1990
DOI: 10.1063/1.102990
|View full text |Cite
|
Sign up to set email alerts
|

Saturation of phase coherence length in GaAs/AlGaAs on-facet quantum wires

Abstract: Phase coherence length Lφ of on-facet quantum wires is determined at temperatures down to 50 mK by three methods: magnetoresistance, conductance fluctuation amplitude, and the conductance fluctuation correlation field. It is found that Lφ saturates below about 0.4 K. This saturation is identified as due to spin-orbit interaction, which has no temperature dependence. This result is supported by positive magnetoresistance under a weak magnetic field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…for the samples made by FIB implantation appears to be dependent on /E F and, therefore, the spin-orbit scattering might be one possibility for the origins of the saturation for a relatively low-mobility and highelectron-denity quantum wire. 9 However, we have never ob-served antilocalization signals due to spin-orbit scattering at low magnetic fields.…”
Section: Origin Of the Phase Breaking Time Saturationmentioning
confidence: 75%
See 2 more Smart Citations
“…for the samples made by FIB implantation appears to be dependent on /E F and, therefore, the spin-orbit scattering might be one possibility for the origins of the saturation for a relatively low-mobility and highelectron-denity quantum wire. 9 However, we have never ob-served antilocalization signals due to spin-orbit scattering at low magnetic fields.…”
Section: Origin Of the Phase Breaking Time Saturationmentioning
confidence: 75%
“…12 For simplicity, we have tried magnetoconductance fitting in a condition that so ӷ i and s ӷ i ; the former condition is tentatively reasonable, since we have never observed antilocalization characteristic to the spin-orbit interaction. 9 On the other hand, a profile of magnetoconductance with s is nearly identical to that without s for a shorter i . The influence of s will be discussed in Sec.…”
Section: ͑1͒mentioning
confidence: 93%
See 1 more Smart Citation
“…This saturation is also reported by other authors ). The spin-orbit scattering is a possible cause as Fukai et al (1990) proposed. The spin-orbit scattering should induce positive magnetoresistance at low magnetic field as Kawaguchi et al (1987) reported in an InAs invcrsion layer.…”
Section: /3mentioning
confidence: 99%
“…Although theoretically, all these mechanisms lead to a diverging l φ with decreasing T [6,7,13,14], experimentally, the increase of l φ with reducing T is often followed by its saturation for T ≤ 2 − 5 K [11,12,15,16]. The saturation of l φ at a finite value instead of its divergence for T → 0 K, which is predicted for electron-electron or electron-phonon interactions, has been a matter of active discourse [14,[17][18][19][20][21][22][23][24][25][26][27][28].In this report, we have inspected the factors that can lead to the saturation of l φ in TIs by measuring both gate-voltage (V G ) and time (t)-dependent conductance fluctuations and magneto-resistance (MR) [27,[29][30][31][32][33][34][35][36]. Conductance fluctuations result from the quantum interference of different electron trajectories, manifested as sample specific, aperiodic fluctuations in the conductance due to varying disorder configuration, Fermi energy, and magnetic field; such fluctuations have been used as a tool to probe the presence of time-reversal symmetry (TRS) breaking disorders, since the saturation of l φ at low T is often attributed to spin-flip scattering processes.…”
mentioning
confidence: 99%